QUALITY OF LEARNING, LEARNING FOR WELL-BEING. CONTRIBUTIONS FOR A MODEL OF SCHOOL AS COMMUNITIES OF LEARNING - Verdasca, José (2015)
This proposal describes the "School Communities of Learning Gulbenkian XXI" project, whose main purpose is to promote the quality of student learning, reflected through the quality of their school results, and manifests itself through the acquisition of basic knowledge within the formal curriculum and reasoning abilities (analytical reasoning, practical reasoning and creativity), resilience and responsibility. Schools that adopt this model of formal education are characterized schools because they are rooted in their communities, open to the world, oriented to the future of new generations and, through a culturally rich and diverse curriculum have as ultimate goal the development of their children and youth potential.